2013
DOI: 10.1016/j.midw.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Working and learning: Post-registration student midwives' experience of the competency assessment process

Abstract: (2005) which is yet to be evaluated from a midwifery perspective.Method A descriptive qualitative study was undertaken once ethical approval had been granted by the University's Ethics Committee. All student midwives (n=20) in one cohort were invited to participate and nine students were interviewed. Interviews were tape recorded.Data were analysed using Burnard's (2006) framework.Findings The process of competency assessment was perceived by many of the students to facilitate continuous assessment of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Support from colleagues and the CPCs were accessed by preceptors in this study, often to confirm or refute their own appraisals, particularly when their decisions were impacted on by not knowing the students. Support from CPCs was also recognised by nursing students in the study by Butler et al (2009) and by midwifery students in the study by Bradshaw et al (2013), both from an Irish context. Butler et al (2009) reported that nurse preceptors perceived the CPCs as supports for nursing students more so than for themselves.…”
Section: Accepted Manuscriptmentioning
confidence: 83%
See 2 more Smart Citations
“…Support from colleagues and the CPCs were accessed by preceptors in this study, often to confirm or refute their own appraisals, particularly when their decisions were impacted on by not knowing the students. Support from CPCs was also recognised by nursing students in the study by Butler et al (2009) and by midwifery students in the study by Bradshaw et al (2013), both from an Irish context. Butler et al (2009) reported that nurse preceptors perceived the CPCs as supports for nursing students more so than for themselves.…”
Section: Accepted Manuscriptmentioning
confidence: 83%
“…The literature highlights issues that nurse and midwife preceptors face when assessing students (Hunt et al 2016, Bradshaw et al 2013,Butler et al 2011, Heffernan 2009., Rutkowski 2007., Duffy 2004., Dolan 2003 in clinical practice from both student and assessor perspective. Challenges identified include dealing with the competing demands of clinical practice, managing the time requirements of assessment, lack of continuity for the preceptor assigned to the student, the confidence and competence of the preceptor and making sense of complex documentation and language in clinical assessment documentation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent challenges in the health care system and its effects on the quality of clinical support offered to midwifery students have become a significant concern for midwifery educators globally [ 3 - 5 ]. High student enrollment rates have subsequently increased the teaching workloads of midwifery educators [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding increase in the number of students placed at clinical sites has also become a challenge for midwifery practitioners. Uncertainties about mentoring roles, negative feelings about teaching, time constraints, and dire staff shortages and resources have negatively affected the clinical support of midwifery students [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%